Genetic variants in Argentinean isolates of Spodoptera frugiperda Multiple Nucleopolyhedrovirus - Niz, José María; Salvador, Ricardo; Ferrelli, María Leticia; Sciocco, Alicia Ines; Romanowski, Víctor; Berretta, Marcelo Facundo (Springer, 2020)
The fall armyworm, Spodoptera frugiperda (JE Smith) is a key pest in the Americas. Control strategies are mainly carried out by use of chemical insecticides and transgenic crops expressing Bacillus thuringiensis toxins. In the last years, resistance of S. frugiperda populations to transgenic corn was reported in different Latin American countries. The baculovirus Spodoptera frugiperda Multiple Nucleopolyhedrovirus (SfMNPV) is a pathogenic agent for the fall armyworm and a potential alternative for its control in integrated pest management strategies. In this work, we analyze some characteristics of two baculovirus isolates collected from maize (SfMNPV-M) and cotton (SfMNPV-C) fields from Argentina. The isolates were compared by restriction enzymes patterns and the analysis reveals the presence of genotypic variants in the SfMNPV-M isolate. We confirmed a deletion by sequencing fragments encompassing egt gene and most part of its contiguous gene (orf A) in a SfMNVP-M genotypic variant. Additionally, we estimated the 50% lethal dose and median survival time of each isolate in bioassays with S. frugiperda larvae.